GREY SYSTEM THEORY SEBAGAI ALTERNATIF ANALISIS STATISTIK TRADISIONAL - Widodo, Agung Mulyo; Simorangkir, Holder; Meria, Lista (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
This Community Service Implementation aims to socialize data processing techniques based on the gray system theory to colleagues in universities. This technique is very helpful in solving the problem of analyzing a fact from phenomena in various scientific fields in real terms which often have uncertainties, related to incomplete data and inaccurate information. This socialization is carried out from a technical perspective, its application and potential problems and challenges in the future, in the context of providing services to the community. Specific targets to be achieved are understanding, knowledge and ability to apply gray system theory. The method used is in the form of counseling with practical delivery through knowledge transfer and the presentation of the roles and functions of the gray system theory so that it is truly acceptable and adds to the essence of knowledge of colleague lecturers and researchers in the university environment.Â Keyword: Grey system, statistic,